LIMITS OF POPULATION FINANCE LITERACY USEFULNESS - Svyatoslav N. Digo (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The author was the first to discuss the issue about the limits of necessary for the population finance literacy in market conditions. The lower limit of finance literacy is determined by the tasks of protecting ordinary market participants against aggressive forms of present day advertising, against groundless finance losses of private profit in conditions of finance and economic crises. Enhancing finance literacy is not a tool of raising confidence to finance institutions but it can promote their responsible work with clients. Asymmetric information on finance markets and professionalism of their trade dealers act as a higher limit of finance literacy usefulness. No changes in it would allow to alter the place of ordinary client on today's finance market.